3rd National Local Government Research Forum (UTS ePRESS, 2013)
The Local Government Researchers' Forum is a biennial forum for local government researchers and practitioners to present current research in the sector and discuss the implications for policy and practice. The format includes streamed sessions, panel discussions and a concluding debate.